Pituitary Adenylate Cyclase Activating Polypeptide Inhibits A10 Dopamine Neurons and Suppresses the Binge-like Consumption of Palatable Food. (1st December 2021) - Le, Nikki; Hernandez, Jennifer; Gastelum, Cassandra; Perez, Lynnea; Vahrson, Isabella; Sayers, Sarah; Wagner, Edward J.
Highlights: VMN PACAP neurons project to the VTA. These neurons inhibit the excitability of A10 dopamine neurons. This occurs via activation of PAC1 receptors and KATP channels. PACAP suppresses binge-feeding behavior in a sexually dimorphic way. Thus, PACAP inhibits the hedonic feeding circuitry and the intake of palatable food. Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) binds to PACAP-specific (PAC1) receptors in multiple hypothalamic areas, especially those regulating energy balance. PACAP neurons in the ventromedial nucleus (VMN) exert anorexigenic effects within the homeostatic energy balance circuitry. Since PACAP can also reduce the consumption of palatable food, we tested the hypothesis that VMN PACAP neurons project to the ventral tegmental area (VTA) to inhibit A10 dopamine neurons via PAC1 receptors and KATP channels, and thereby suppress binge-like consumption. We performed electrophysiological recordings in mesencephalic slices from male PACAP-Cre and tyrosine hydroxylase (TH)-Cre mice. Initially, we injected PACAP (30 pmol) into the VTA, where it suppressed binge intake in wildtype male but not female mice. Subsequent tract tracing studies uncovered projections of VMN PACAP neurons to the VTA. Optogenetic stimulation of VMN PACAP neurons in voltage clamp induced an outward current and increase in conductance in VTA neurons, and a hyperpolarization and decrease in firing in current clamp. These effects were markedly attenuated by the KATP channel blocker tolbutamide (100 μM) and PAC1 receptor antagonist PACAP6–38 (200 nM). In recordings from A10 dopamine neurons in TH-Cre mice, we replicated the outward current by perfusing PACAP1–38 (100 nM). This response was again completely blocked by tolbutamide and PACAP6–38, and associated with a hyperpolarization and decrease in firing. These findings demonstrate that PACAP activates PAC1 receptors and KATP channels to inhibit A10 dopamine neurons and sex-dependently suppress binge-like consumption. Accordingly, they advance our understanding of how PACAP regulates energy homeostasis via the hedonic energy balance circuitry.